Konsep Al-Qur’an sebagai Sumber Utama dalam Hukum Islam - Tentiyo Suharto; Asmuni; Tuti Anggraini (Jurnal Multidisiplin Madani, 2022)
This research is a library research whose data is through library sources, namely library research through library research. The study of literature (library research) is closely related to theoretical studies and other references related to the relevance of the use of the Koran in sharia economic reviews. The contents of the Qur'an are creed, worship, morals, law, warning/tadzkir, history or stories and signs for those who carry science and technology. The language style of the Qur'an in conveying the law is not burdensome or troublesome, does not add to the burden/demand and is gradual in ordering something. Qath'i and Zhanni are quite complicated discussions among Ushuliyun or ushul fiqh scholars when dealing with the force of law (hujjah a proposition). We can understand the position of the Qur'an as a source of law from the views of the imams of the four schools of thought, namely Imam Abu Hanifa, Imam Malik, Imam Shafi'i, and Imam Ahmad Ibn Hambal.